A Spatial Regression Analysis on the Effect of Neighborhood-Level Trust on Cooperative Behaviors: Comparison With a Multilevel Regression Analysis - Takagi, Daisuke; Shimada, Takahito (Frontiers in Psychology, 2019)
There is no reason to suppose that neighborhood effects based on residents’ trust vary according to administrative boundaries. We examined the relationship between neighborhood trust and cooperative behaviors using the spatial Durbin model which assumed that people are influenced by closer neighbors regardless of administrative boundaries, comparing the results with those of the multilevel model. We used data from 476 residents in Arakawa Ward, Tokyo, Japan. For each respondent, we assigned a unique ‘neighborhood trust’ value weighted by the inverse distance between the respondent and all other respondents as an independent variable. The dependent variables were perceived neighbors’ cooperative behaviors and respondents’ own cooperative behaviors. The spatial Durbin model showed that spatially-weighted neighborhood trust was positively associated with cooperative behaviors. Meanwhile, the multilevel models did not show the statistically significant effect of neighborhood trust. We concluded that the spatial model might model the neighborhood effects in society more precisely.